The predictive value of neutrophil to lymphocyte ratio for abortion: a systematic review and meta-analysis - Wang, Mi; Yue, Rui; Xi, Jun; Yan, Fang (Frontiers in Medicine, 2025)
BackgroundAbortion usually refers to the loss of pregnancy before viability. Despite a potential link between neutrophil-lymphocyte ratio (NLR) levels and abortion, inconclusive findings remain. This review aimed to comprehensively appraise the predictive utility of NLR levels in abortion, offering a new approach to clarify its potential role as a biomarker.MethodsPubMed and Cochrane Library were searched for relevant cohort and case–control studies until September 2024. Odds ratio (OR) or weighted mean difference (WMD) with 95% CI of abortion were computed. Subgroup analyses were implemented to clarify potential sources of heterogeneity.ResultsHigher NLR levels were linked to an enhanced risk of abortion as a continuous (WMD, 0.58; 95% CI: 0.29, 0.88) and dichotomous variable (OR, 1.33; 95% CI: 1.03, 1.72). In subgroup analyses, pooled results from studies with NLR cut-off>3, Asia populations, missed abortion, spontaneous abortion, and mean age>30 demonstrated an increased risk of abortion. In continuous NLR for predicting abortion, retrospective study, Europe populations, threatened abortion, recurrent pregnancy loss, and abortion had an enhanced risk of abortion for higher NLR levels as a dichotomous variable.ConclusionPooled analyses demonstrated that higher NLR levels may predict abortion. Further investigations need to determine whether these findings can be generalized to all populations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/485726.